2008
DOI: 10.1111/j.1471-4159.2008.05524.x
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic drugs increase N‐acetylaspartate and N‐acetylaspartylglutamate in SH‐SY5Y human neuroblastoma cells

Abstract: N‐Acetylaspartate (NAA) and N‐acetylaspartylglutamate (NAAG) are related neuronal metabolites associated with the diagnosis and treatment of schizophrenia. NAA is a valuable marker of neuronal viability in magnetic resonance spectroscopy, a technique which has consistently shown NAA levels to be modestly decreased in the brains of schizophrenia patients. However, there are conflicting reports on the changes in brain NAA levels after treatment with antipsychotic drugs, which exert their therapeutic effects in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…NAAG modulates the glutamatergic system through a presynaptic metabotropic glutamate receptor (mGluR2/3) [73][74][75] or NMDA receptors [76]. Arun et al (2008) found that antipsychotic drugs increased the NAA and NAAG levels in dopaminergic-like human neuroblastoma cells and hypothesized, that D2 blockade may modulate the NAAG and NAA expression. NAAG is also reported to reduce glutamate excitotoxicity via its mGluR2/3 receptor agonism.…”
Section: Possible Mechanisms Underlying the Impact Of Antipsychotics mentioning
confidence: 99%
See 1 more Smart Citation
“…NAAG modulates the glutamatergic system through a presynaptic metabotropic glutamate receptor (mGluR2/3) [73][74][75] or NMDA receptors [76]. Arun et al (2008) found that antipsychotic drugs increased the NAA and NAAG levels in dopaminergic-like human neuroblastoma cells and hypothesized, that D2 blockade may modulate the NAAG and NAA expression. NAAG is also reported to reduce glutamate excitotoxicity via its mGluR2/3 receptor agonism.…”
Section: Possible Mechanisms Underlying the Impact Of Antipsychotics mentioning
confidence: 99%
“…On the other hand, changes in NAA may affect the glutamatergic system, via NAAG (N-acetylaspartylglutamate), which is believed to be formed biosynthetically from NAA and its concentration may be NAA-dependent [71] (Fig. 2).…”
Section: Possible Mechanisms Underlying the Impact Of Antipsychotics mentioning
confidence: 99%
“…Given the differences in their targets from those of the typical and atypical antipsychotic drugs, the discovery of the efficacy of group II mGluR agonists and NAAG peptidase inhibitors in these animal models of schizophrenia and in clinical trials using the agonists represents a potentially important breakthrough in antipsychotic drug design. Interestingly, it may turn out that current antipsychotic treatments may already achieve some of their effects via NAAG in as much as clozapine and haloperidol increase NAAG synthesis in a neuroblastoma cell line (23).…”
Section: Discussionmentioning
confidence: 99%
“…Brains were removed rapidly (within approximately 1 min) and the left injured hemispheres were isolated and homogenized immediately in ice-cold PBS (10% wt=vol) to be used for the estimation of NAA and ATP. NAA concentrations were determined using methods described earlier (Arun et al, 2008). Briefly, 50 ml of the 10% homogenate made above was mixed with 500 ml of 90% methanol in water, mixed vigorously, and centrifuged at 10,000g for 10 min at 48C.…”
Section: Estimation Of N-acetylaspartatementioning
confidence: 99%